MENINGKATKAN HASIL BELAJAR GULING DEPAN PADA PEMBELAJARAN SENAM LANTAI MELALUI MODEL PERMAINAN : Meningkatkan Hasil Belajar Guling Depan Pada Pembelajaran Senam Lantai Melalui Model Permainan - Tho Chandra, Dini; Syamsulrizal, Syamsulrizal; Razali, Razali; Iqbal, Muhammad (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2021)
The purpose of the study. To improve the learning outcomes of front roll in floor gymnastics learning through a game model at Kemala Bhayangkari 2 Junior High School, South Jakarta. Materials and methods. The method in this research is classroom action which follows the model of Kemmis and Taggart theory. This research is planned for 3 cycles where each cycle has 4 stages, namely planning, acting, observing and reflecting. The research time was 3 months with 30 students as research subjects, while data were collected through tests, interviews and observations. Results. The average score of students in the initial conditions was 70.46 with a percentage of completeness of 38.46%. This condition experienced an increase in the average score of students in the first cycle, which was 73.08 and the percentage of completeness was 57.69%. In the second cycle, the average value of the front roll ability of students again increased by 82.82 with a percentage of completeness of 80.77%. Conclusions. This shows that the previously set target has been achieved so that the research is stopped in cycle II.